VERSO NUOVE FORME DI DOCUMENTAZIONE ARCHEOLOGICA LA MODELLAZIONE TRIDIMENSIONALE TRA APPLICAZIONI E LIMITI DI UTILIZZO - Rapanà , Matteo (Archeomatica, 2012)
Il vasto settore dei beni culturali dispone di una serie di tecniche non invasive per il rilevamento e la visualizzazione di manufatti e di elementi naturali di differente forma e dimensione. Fotogrammetria, modellazione mediante laser scanner, immagini aeree o satellitari permettono, infatti, l'elaborazione di modelli tridimensionali estremamente accurati che possono costituire un prezioso strumento in numerose attività tra cui visualizzazione, analisi, catalogazione, monitoraggio, ecc. New form of documentation Modern 3D modeling techniques allow the creation of accurate, realistic and measurable digital 3D model of cities, buildings, terrains, artifacts and archaeological sites. Although these systems are broadly used within the wide sector of the Cultural Heritage, the aforementioned techniques are sporadically used in archaeology due to several factors. The model of St. Martino's Church was realized not only for the visualization but especially for the study of the 3D application in archaeology and compare the information provided by this techniques with data obtained by traditional techniques even it is possible. Precise measurements of distances, surfaces, thicknesses and volumes of the structures or of particular architectural elements were performed. Particular elements were also recognized and emphasized thanks to the creation of the 3D model. These elements have been inserted into a database according to their characteristics and this led to the generation of several 3D thematic maps (i.e. building phase maps or litho topes).